Mechanisms of Bacterial Superinfection Post-influenza: A Role for Unconventional T Cells - Paget, Christophe; Trottein, François (Frontiers in Immunology, 2019)
Despite the widespread application of vaccination programs and antiviral drug treatments, influenza viruses are still among the most harmful human pathogens. Indeed, influenza results in significant seasonal and pandemic morbidity and mortality. Furthermore, severe bacterial infections can occur in the aftermath of influenza virus infection, and contribute substantially to the excess morbidity and mortality associated with influenza. Here, we review the main features of influenza viruses and current knowledge about the mechanical and immune mechanisms that underlie post-influenza secondary bacterial infections. We present the emerging literature describing the role of “innate-like” unconventional T cells in post-influenza bacterial superinfection. Unconventional T cell populations span the border between the innate and adaptive arms of the immune system, and are prevalent in mucosal tissues (including the airways). They mainly comprise Natural Killer T cells, mucosal-associated invariant T cells and  T cells. We provide an overview of the principal functions that these cells play in pulmonary barrier functions and immunity, highlighting their unique ability to sense environmental factors and promote protection against respiratory bacterial infections. We focus on two major opportunistic pathogens involved in superinfections, namely Streptococcus pneumoniae and Staphylococcus aureus. We discuss mechanisms through which influenza viruses alter the antibacterial activity of unconventional T cells. Lastly, we discuss recent fundamental advances and possible therapeutic approaches in which unconventional T cells would be targeted to prevent post-influenza bacterial superinfections.